2001
DOI: 10.1097/00005768-200102000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of isometric exercise on pain perception and blood pressure in men and women

Abstract: It is concluded that: 1) men and women differed in PT, SBP, and DBP before ISO EX; and 2) analgesia after ISO EX is observed more consistently in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
86
4
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 0 publications
6
86
4
3
Order By: Relevance
“…18 The state portion of the STAI was administered three times, before the initial pain test and again immediately after each of the two pressure pain tests. Because performance of maximal voluntary contractions (MVC) has been found to influence pain reports in young 9,14 and older 21 adults, determination of left elbow flexor MVC force was performed during the of Sports Medicine and permission has been granted for this version to appear in e-Publications@Marquette. American College of Sports Medicine does not grant permission for this article to be further copied/distributed or hosted elsewhere without the express permission from American College of Sports Medicine.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…18 The state portion of the STAI was administered three times, before the initial pain test and again immediately after each of the two pressure pain tests. Because performance of maximal voluntary contractions (MVC) has been found to influence pain reports in young 9,14 and older 21 adults, determination of left elbow flexor MVC force was performed during the of Sports Medicine and permission has been granted for this version to appear in e-Publications@Marquette. American College of Sports Medicine does not grant permission for this article to be further copied/distributed or hosted elsewhere without the express permission from American College of Sports Medicine.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Both distraction and stress can independently reduce pain (Fernandez and Turk 1989;Fields and Basbaum 1999) and are likely to contribute to pain-evoked hypoalgesia, as painful stimuli are not only painful but also distracting and stressful. Sex differences in both distraction- (Weisenberg et al 1995;Bentsen et al 1999;Unrod et al 2004) and stress-evoked hypoalgesia (Koltyn et al 2001;Rhudy and Meagher 2001;Sternberg et al 2001;Girdler et al 2005) have been reported. Thus, pain-evoked hypoalgesia may represent the combined effects of multiple sex-sensitive factors.…”
Section: Introductionmentioning
confidence: 99%
“…35 In addition, women have higher pain responses to pressure applied onto muscles than men 1,5,7,25,32,43,44,67 with an exception located. 51 Furthermore, women have greater muscle pain in response to intramuscular injections of algesic substances than men 4,27,79 with one exception located.…”
Section: Introductionmentioning
confidence: 99%